2015
DOI: 10.1007/s11103-015-0329-7
|View full text |Cite
|
Sign up to set email alerts
|

The rice transcription factor OsWRKY47 is a positive regulator of the response to water deficit stress

Abstract: higher sensitivity to drought and reduced yield, while plants overexpressing OsWRKY47 were more tolerant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
64
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(69 citation statements)
references
References 62 publications
(70 reference statements)
1
64
0
Order By: Relevance
“…Nuruzzaman et al [11] identified five OsWRKY genes expressed at higher levels in drought-tolerant rice compared with those in drought-susceptible rice under experimental water-deficit conditions. Overexpression of OsWRKY47 increased both the yield and drought tolerance compared with wild-type plants [12]. Meng et al [13] discovered that 10 selected WRKY genes showed differential expression patterns under waterlogging and drought stress in an apple rootstock.…”
Section: Introductionmentioning
confidence: 99%
“…Nuruzzaman et al [11] identified five OsWRKY genes expressed at higher levels in drought-tolerant rice compared with those in drought-susceptible rice under experimental water-deficit conditions. Overexpression of OsWRKY47 increased both the yield and drought tolerance compared with wild-type plants [12]. Meng et al [13] discovered that 10 selected WRKY genes showed differential expression patterns under waterlogging and drought stress in an apple rootstock.…”
Section: Introductionmentioning
confidence: 99%
“…When overexpressed in rice, OsbZIP23, OsbZIP46 and OsbZIP71 indicated a positive correlation with yield under drought by regulating the expression of dehydrins, membrane transporters like OsNHX1 and COR413-TM1, and ABFs (Xiang et al, 2008, Tang et al, 2012. Belonging to the GRAS family, OsGRAS23 was found to contribute to yield increase under drought through regulation of ROS scavenging (Raineri et al, 2015, Guo et al, 2016a.…”
Section: Gene Discovery and Regulatory Mechanismsmentioning
confidence: 98%
“…Expression analysis of the WRKY family of TFs in rice identified OsWRKY45 and OsWRKY11 as heat inducible, while overexpression of OsWRKY11 under the control of HSP101 promoter showed tolerance to HTS indicated by higher survival rates and lower leaf wilting (Wu et al, 2009). OSWRKY47, MID1 (MYB Important for Drought Response1) were also found to contribute to drought tolerance and hence yield by modulating the expression of Calmodulin-Binding Protein (CaMBP) (Raineri et al, 2015, Guo et al, 2016a. Two ABA-inducible TFs: OsAREB1 and OsSNAC3 were also induced by heat, and when overexpressed in rice and Arabidopsis, the transgenic plants showed heat tolerance owing to efficient scavenging of ROS and regulation of genes from the ABA signaling pathway (Jin et al, 2010, Fang et al, 2015.…”
Section: Gene Discovery and Regulatory Mechanismsmentioning
confidence: 99%
“…In rice, 11 OsWRKY genes showed variable responses to salt, polyethylene glycol (PEG), and cold or heat stresses [25]. Overexpression of OsWRKY47 increased both the drought tolerance and yield compared with wild-type plants [26]. In mulberry, Morus013217 and Morus002784 show high accumulation in response to cold and salt stresses.…”
Section: Introductionmentioning
confidence: 99%